Aid effectiveness: Looking at the aid-social capital-growth nexus - Mina Baliamoune-Lutz; George Mavrotas (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2008)
We examine the impact of institutional quality and social capital on aid effectiveness. We find strong evidence that social capital and institutions enhance aid effectiveness. Moreover, once we account for the role of social capital and institutions, the impact of policies tend to disappear. These findings have important policy implications as they indicate that conditioning aid allocation on good policies may not lead to an optimal (or fair) allocation of aid, as countries with high social capital at the macro level could actually make good use of aid regardless of the quality of policy. This casts doubt on the conclusions in Burnside and Dollar (2000) and the policy lessons derived from their findings.
Keywords: F35; 330; aid effectiveness; social capital; institutions; growth; Entwicklungshilfe; Social Capital; Institutionelle Infrastruktur